Carbonate sedimentation in seagrass beds on Ishigaki‐jima, Ryukyu Islands, southwestern Japan. (June 2015) - Fujita, Keita; Asami, Ryuji; Takayanagi, Hideko; Iryu, Yasufumi
Abstract In order to investigate biota and sedimentary facies, and to delineate processes of carbonate sedimentation in seagrass beds, we conducted sedimentological investigations along three onshore–offshore transects at two sites (Nagura and Yoshihara) on Ishigaki‐jima, Ryukyu Islands. Along the transects, the seagrass beds extended seaward 20–40 m from shore, and their widths parallel to the shore ranged from 60 to >110 m. The seagrass was dominated by Thalassia hemprichii, Cymodocea rotundata and subordinate C. serrulata. Seasonal changes in seagrass coverage were evident, with mean coverage relatively higher in summer and fall (July and October) than in winter and spring (January and April). The surface sediment throughout the seagrass beds was dominated by medium to very coarse sand‐sized bioclasts displaying grainstone/packstone fabrics. Bioclasts were dominated by corals and coralline algae, with lesser benthic foraminifers, mollusks, echinoids, and Halimeda. The grainstone/packstone was underlain by gravelly sediment with coral clasts, showing a rudstone fabric, at the Nagura Site. The lower part of the core sediment was blackened, indicating a reducing environment. Two dates of corals collected at the Nagura and Yoshihara sites (24.5 cm and 16.5 cm below the sea bottom) were 2781–2306 and 4374–3805 cal BP (2σ age range), respectively, suggesting extremely low sedimentation rates (<0.1 mm/year). Sediment influx was higher during July–January than during January–July. The relatively large influx during summer and fall is caused by massive sediment transport during typhoons and storms. The total sediment influx (i.e., suspension‐load sediment transportation) is 74–96 kg CaCO3/m2/year at the Nagura Site and 21–57 kg CaCO3/m2/year at the Yoshihara Site. Sediment influx was significantly greater in the seagrass beds than in surrounding areas, providing supporting evidence for an sediment trapping function of seagrass beds. Our data indicate that seagrass beds in the Ryukyu Islands are characterized by high sediment fluxes and extremely low sedimentation rates.